2014
DOI: 10.1016/j.pedneo.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Preterm Breast Milk Nutrient Content in the First Month

Abstract: The longitudinal study revealed significant changes in macronutrient contents and secretory IgA concentration in preterm milk over the 4-6 week period, which is compatible with the results of previous studies. The quantification of phosphate in preterm breast milk was lower than the normal range, suggesting that close monitoring of body bone mass may be indicated. More studies are warranted to evaluate the clinical significance of alterations of major milk components during the postnatal stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
3
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 25 publications
7
43
3
7
Order By: Relevance
“…This is consistent with the results from multiple studies (Hennart et al 1991; Molinari et al 2013; Reddy et al 1977; Sanchez-Pozo et al 1986; Shashiraj et al 2006; Trend et al 2015). Differing results were presented by Hsu et al 2014; they found a stable LF concentration in the first month in the milk from mothers from Taiwan; however, they started collecting samples 5–7 days postpartum. Van der Strate et al also found no significant difference during the course of lactation, although they highlight a 7-fold decrease in LF concentration from colostrum compared to samples from 2 weeks after birth (van der Strate et al 2001).…”
Section: Factors Affecting Lf Concentration In Breast Milkmentioning
confidence: 97%
See 1 more Smart Citation
“…This is consistent with the results from multiple studies (Hennart et al 1991; Molinari et al 2013; Reddy et al 1977; Sanchez-Pozo et al 1986; Shashiraj et al 2006; Trend et al 2015). Differing results were presented by Hsu et al 2014; they found a stable LF concentration in the first month in the milk from mothers from Taiwan; however, they started collecting samples 5–7 days postpartum. Van der Strate et al also found no significant difference during the course of lactation, although they highlight a 7-fold decrease in LF concentration from colostrum compared to samples from 2 weeks after birth (van der Strate et al 2001).…”
Section: Factors Affecting Lf Concentration In Breast Milkmentioning
confidence: 97%
“…Similarly, Mehta & Petrova (2011) have found that very preterm delivery was associated with higher levels of sIgA, lysozyme and adiponectin in transitional milk, but lower LF and leptin (p<0.05). Moreover, some authors have also performed studies that did not find a significant difference between preterm and term milk (Britton 1986; Hsu et al 2014; López et al 1997; Molinari et al 2013; Ronayne de Ferrer et al 2000). Broadhurst et al (2015) have published a recent study that included 30 mothers at their second and fifth week of lactation, organized in three groups according to gestational age (very premature, premature and full term), and found no significant differences.…”
Section: Factors Affecting Lf Concentration In Breast Milkmentioning
confidence: 99%
“…Studies confirmed that colostrum contains higher concentrations of immune-protective agents compared with mature human milk, such as lactoferrin, lysozyme, and sIgA (9)(10)(11). Therefore, giving colostrum as soon as excreted from their mother can provide more immunological support for immature preterm newborns.…”
Section: Introductionmentioning
confidence: 93%
“…The sIgA levels in breast milk decrease over time during the postpartum period [8]. Recent studies have identified no difference in breast milk sIgA concentration of preterm versus term breast milk [6,8], although Mehta and Petrova identified that preterm milk contains a higher concentration of sIgA in the first six to eight days of lactation [9].…”
Section: Maternal Soluble Igamentioning
confidence: 99%